Getting even - Billingsley, ReShonda Tate. (New York : Pocket Books, 2008)
Camille and Alexis find their happiness and friendship tested when they discover they are dating the same boy, a realization that teaches them important lessons about vengeance and also strains relations in their Good Girlz church group that includes Jasmine and Angel. Includes book club discussion questions and activities plus an interview with the author.
Keywords: Friendship -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Forgiveness -- Juvenile fiction; Revenge -- Juvenile fiction; Christian life -- Juvenile fiction; African Americans -- Juvenile fiction